2017
DOI: 10.1007/s00775-017-1466-z
|View full text |Cite
|
Sign up to set email alerts
|

The DNA sequence specificity of bleomycin cleavage in a systematically altered DNA sequence

Abstract: Bleomycin is an anti-tumour agent that is clinically used to treat several types of cancers. Bleomycin cleaves DNA at specific DNA sequences and recent genome-wide DNA sequencing specificity data indicated that the sequence 5'-RTGT*AY (where T* is the site of bleomycin cleavage, R is G/A and Y is T/C) is preferentially cleaved by bleomycin in human cells. Based on this DNA sequence, we constructed a plasmid clone to explore this bleomycin cleavage preference. By systematic variation of single nucleotides in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…More recently, updated technology using capillary electrophoresis with laser-induced fluorescence (CE-LIF) and automated DNA sequencers, has permitted a more accurate and precise determination of the DNA sequence specificity of bleomycin DNA damage in longer purified DNA sequences [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. In addition, the use of separate 5′- and 3′-end-labelling in a DNA sequence specificity study contributes to the precision of the process by greatly reducing end-label bias [ 78 , 79 ]. It should be noted that experiments with end-labelled DNA mainly detect single-strand breaks (see below).…”
Section: Bleomycin Cleavage Specificity With Purified Dna Using Upmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, updated technology using capillary electrophoresis with laser-induced fluorescence (CE-LIF) and automated DNA sequencers, has permitted a more accurate and precise determination of the DNA sequence specificity of bleomycin DNA damage in longer purified DNA sequences [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. In addition, the use of separate 5′- and 3′-end-labelling in a DNA sequence specificity study contributes to the precision of the process by greatly reducing end-label bias [ 78 , 79 ]. It should be noted that experiments with end-labelled DNA mainly detect single-strand breaks (see below).…”
Section: Bleomycin Cleavage Specificity With Purified Dna Using Upmentioning
confidence: 99%
“…It was observed that the preferred nucleotide sequence for high intensity bleomycin cleavage was 5′-YYGT*AW (where W is A or T) ( Table 1 ). The DNA sequence that had the highest intensity of bleomycin cleavage was 5′-TCGT*AT and the seven highest intensity bleomycin cleavage sites conformed to the 5′-YYGT*AW consensus sequence [ 79 ]. This study permitted a precise evaluation of crucial neighbouring nucleotides that produced high intensity bleomycin DNA cleavage sites.…”
Section: Bleomycin Cleavage Specificity With Purified Dna Using Upmentioning
confidence: 99%
See 2 more Smart Citations
“…The same reaction affinity was observed in our study (marked in Figure B), with two hotspots containing more 5′‐GT‐3′ and 5′‐GC‐3′ exhibiting high frequency of cleavage (P3–P6, P15–P18). P10 and P11 targeting of 5′‐ATGTA‐3′, which was also considered a hot sequence for the peplomycin approach, was further enhanced in the nucleosomal DNA structure, as shown by the observed increased reactivity of P11. In addition, except for P10 and P11, although some very low intensity peaks showed up in the nucleosomal core region for peplomycin⋅Fe II ‐mediated cleavage, about 5.6‐fold (47.1–8.4 %) suppression was observed, which was highly consistent with previous reports of bleomycin…”
Section: Resultsmentioning
confidence: 99%